Core Biopsy Diagnosis of ALK Positive Inflammatory Myofibroblastic Tumor of Lung: An Interesting Case - Ritesh SACHDEV; Ishani MOHAPATRA; Shalini GOEL; Kulbir AHLAWAT; Neelam SHARMA (Federation of Turkish Pathology Societies, 2020)
Inflammatory myofibroblastic tumor (IMT) of lung is a rare tumor, accounting for ~0.7% of all lung tumors with varied clinical and radiological presentations. The origin of this tumor is unknown but some studies suggest that it might be a true neoplasm as some mutations on chromosome 2p23 of anaplastic lymphoma kinase (ALK) have been found to be related to this tumor. The morphology of IMT is quite vague and the histopathological diagnosis is predominantly given on excision specimens; in fact, only 6.3% of cases are diagnosed based on analysis of biopsy specimens alone. We illustrate a case of IMT diagnosed in a young male on core biopsy, where the case presented with a large tumor in the lung with metastases to multiple sites that was hence unresectable. Post 3 months of treatment with Crizotinib, there was significant reduction in the tumor size. Another interesting finding was that the ALK immunostain, which helped immensely in the diagnosis, was appreciated better on the Ventana platform rather than on the Dako platform.